One Dimensional Mathematical Model of Re-Ignition Characteristics - Tri Poespowati (ASEAN Journal of Chemical Engineering, 2009)
Re-ignition of a wood-based object essentially comprises three overlapping phases; these are the heat-up phase, the extinguishment phase, and the re-heat-up phase. A one-dimensional mathematical model was developed in this study to simulate multiple consecutive ignitions associated with re-ignition process within a porous material. The model focuses on the treatment of heat transfer in porous media that is assumed to be one-dimensional within a homogeneous sample. The effect of porosity is incorporated through the inclusion of an effective thermal conductivity. Our experience indicates that the ignition temperatures and ignition delay times obtained from this approach are in good agreement with relevant experimental data.